Redescription of Streptaxis mouhoti Pfeiffer, 1863 and Streptaxis strangulatus Möllendorff, 1894 (Eupulmonata: Streptaxidae) from Peninsular Thailand and Their Assignment to a New Genus - Chunkhajorn, Sittichai; Rungruangdejwattana, Pongpisit; Sutcharit, Chirasak; Siriboon, Thanit (Tropical Natural History, 2023)
Two species of the family Streptaxidae found in Peninsular Thailand are redescribed and assigned to a new genus, Panhartemis gen. nov. The new genus has two new distinctive species, Panhartemis strangulatus comb. nov. and Panhartemis mouhoti comb. nov., from isolated limestone karsts in western Thailand. Panhartemis Siriboon, gen. nov. exhibits an oblique-cylindrical shell shape, elevated conical spire, last whorl slightly axially deflected, and penial hooks separated by elevated reticulated folds; none of these characteristics occur in other streptaxids. Details of the genital anatomy and the radula of the two species are provided for the first time. The current study advances knowledge of the streptaxid land snail species in Peninsular Thailand and emphasizes the value of limestone habitats for preserving biodiversity.